Developments in rare bone diseases and mineral disorders. (January 2018) - Bacon, Siobhan; Crowley, Rachel
In the last decade, there have been a number of significant advances made in the field of rare bone diseases. In this review, we discuss the expansion of the classification system for osteogenesis imperfecta (OI) and the resultant increase in therapeutic options available for management of OI. Bisphosphonates remain the most widely used intervention for OI, although the effect on fracture rate reduction is equivocal. We review the other therapies showing promising results, including denosumab, teriparatide, sclerostin, transforming growth factor β inhibition and gene targeted approaches. X-linked hypophosphataemia (XLH) is the most common heritable form of osteomalacia and rickets caused by a mutation in the phosphate regulating endopeptidase gene resulting in elevated serum fibroblast growth factor 23 (FGF23) and decreased renal phosphate reabsorption. The traditional treatment is phosphate replacement. We discuss the development of a human anti-FGF23 antibody (KRN23) as a promising development in the treatment of XLH. The current management of primary hypoparathyroidism is replacement with calcium and active vitamin D. This can be associated with under or over replacement and its inherent complications. We review the use of recombinant parathyroid hormone (1–84), which can significantly reduce the requirements for calcium and vitamin D resulting in greater safety and quality of life for individuals with hypoparathyroidism. The use of receptor activator of nuclear factor κB ligand infusions in the treatment of a particular form of osteopetrosis and enzyme replacement therapy for hypophosphatasia are also discussed.